Preventable maternal deaths: a 6-year retrospective study of healthcare deficiencies in Yaoundé’s teaching hospitals, Cameroon - Felix, Essiben; Madye Ange, Ngo Dingom; Jivir, Nsahlai Christiane; Steve-Alan, Yemeli Kematio; Henri Leonard, Mol; Pascal, Foumane (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: This study aimed to investigate the management deficiencies contributing to maternal mortality in teaching hospitals in Yaoundé. Methods: This was a retrospective cross-sectional analytical study conducted from November 2024 to April 2025 at the Yaoundé University Teaching Hospital (CHUY), the Yaoundé Central Hospital (HCY), and the Yaoundé Gynaeco-Obstetric and Paediatric Hospital (HGOPY). We analyzed maternal death review reports and medical records of 257 cases occurring between January 2019 and April 2025. We examined the circumstances of death, identified management deficiencies, and investigated the determinants of each failure. Data were analyzed using SPSS version 25.0. Results: The median age of the deceased women was 30 years (range: 16–45). Most deaths occurred postpartum (63.0%; 162/257), and the majority of patients (80.9%; 207/257) were referrals from other health facilities. Direct obstetric causes accounted for 91.1% (234/257) of deaths, dominated by hemorrhage (47.0%; 110/234) followed by hypertensive complications (29.1%; 68/234). Severe malaria (52.2%; 12/23) and HIV complications (17.4%; 4/23) were the most frequent indirect causes. The primary management deficiencies identified were delays in reaching the health facility (79.8%; 205/257) and delays in receiving adequate care (30.7%; 79/257). These failures were primarily attributable to inadequate transportation during referral (75.5%; 194/257), delayed access to diagnostic investigations (30.0%; 77/257), late referrals (25.7%; 66/257), and stockouts of essential medicines (17.9%; 46/257) or blood products (16.3%; 42/257). Most of the deaths analyzed were preventable (88.7%; 228/257). Conclusions: The analysis of maternal deaths highlighted substantial structural and organizational deficiencies. Improved adherence to clinical management protocols, together with reliable provision of essential medical supplies are crucial for reducing maternal mortality.